2022
DOI: 10.1029/2022tc007430
|View full text |Cite
|
Sign up to set email alerts
|

Nappe Imbrication Within the Phyllite‐Quartzite Unit of West Crete: Implications for Sustained High‐Pressure Metamorphism in the Hellenide Subduction Orogen, Greece

Abstract: We report four K‐Ar fault‐gouge and eight U‐Pb calcite ages from the high‐pressure Phyllite‐Quartzite Unit (PQ) and the overlying, strongly thinned non‐high‐pressure Tripolitza and Pindos units of western Crete, Greece. We relate consistent 26–21 Ma fault‐gouge ages to a discrete top‐to‐the‐S, brittle‐ductile, contractional shear zone (Intra‐PQ Thrust) that formed during high‐pressure conditions within the Phyllite‐Quartzite Unit. The Intra‐PQ Thrust separates the Phyllite‐Quartzite Unit into an upper and a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 121 publications
1
9
0
Order By: Relevance
“…In the southern Peloponnese, this second phase of exhumation occurred during the Middle to Late Miocene (Marsellos et al, 2010). Ring et al (2022) date a late extensional phase as younger than 12-11 Ma in Crete, and Grasemann et al (2019) have demonstrated that the PQ Unit in central Crete was exhumed above the brittleductile transition at 15 Ma. Its timing in the Northern Peloponnese is so far unconstrained, but is likely to have started later, during the Late Miocene (Athanassas et al, 2021).…”
Section: Exhumation Of the Phyllite-quartzite Unit And Formation Of L...mentioning
confidence: 89%
See 2 more Smart Citations
“…In the southern Peloponnese, this second phase of exhumation occurred during the Middle to Late Miocene (Marsellos et al, 2010). Ring et al (2022) date a late extensional phase as younger than 12-11 Ma in Crete, and Grasemann et al (2019) have demonstrated that the PQ Unit in central Crete was exhumed above the brittleductile transition at 15 Ma. Its timing in the Northern Peloponnese is so far unconstrained, but is likely to have started later, during the Late Miocene (Athanassas et al, 2021).…”
Section: Exhumation Of the Phyllite-quartzite Unit And Formation Of L...mentioning
confidence: 89%
“…The kinematics of the Cretan detachment and associated exhumation of the PQ Unit in the southern Peloponnese and Crete are a subject of debate, with a range of exhumation models proposed, including: (a) a cold metamorphic core complex (van Hinsbergen & Meulenkamp, 2006); (b) post‐accretion bivergent extension (Fassoulas, 1999); (c) syn‐accretion extension (Jolivet et al., 1994, Jolivet et al., 1996); and (d) wedge extrusion within a subduction channel (Grasemann et al., 2019; Jolivet, Trotet, et al., 2010; Ring & Yngwe, 2018; Ring et al., 2022). In the Northern Peloponnese, the wedge extrusion model explains the presence of both ductile top to ENE and WSW shear bands within the PQ Unit as well as the presence of a more co‐axial style of deformation within the core of the exhuming unit (Kotowski et al., 2022; Lamont et al., 2020; Ring et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10–11 Ma, which are slightly younger than U-Pb calcite ages reported from the nappe contact between TPU/Pindos Unit and the lower nappes (12–13 Ma, Ring et al . 2022). The younger generation was formed between 7 and 9 Ma (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(1) K-Ar and 39 Ar- 40 Ar ages of white mica obtained from phyllites of the Phyllite-Quartzite Unit s.str. of central and western Crete range from 24 to 19 Ma regarded as the time of HP-LT metamorphism (Seidel et al 1982; Jolivet et al 1996; Ring et al 2022). (2) Fission-track ages of zircon yielded an arithmetic mean sample age at 18.6 ±1.9 Ma suggesting cooling below ca.…”
Section: Discussionmentioning
confidence: 99%